Second line therapy: type 2 diabetic subjects failing on metformin GLP-1/DPP-IV inhibitors versus sulphonylurea/insulin: For GLP-1/DPP-IV inhibitors - Kumar, Ajay (Diabetes/metabolism research and reviews, 2012)
Summary Following diagnosis, type 2 diabetic subjects are invariably treated with life style modifications and metformin. However, majority of these subjects require addition of another therapeutic agent singly or in combination; with or without insulin within few months to few years. For several decades, sulphonylureas and insulin have been the second line agent of choice. Clinical practice guidelines also suggest a similar approach. Subsequently thiazolidinediones, alpha glucose inhibitors and other agents were added to therapeutic armamentarium. Unfortunately, none of these treatment options could address the issue of progressive decline in beta cell function. Furthermore, they are responsible for unacceptable incidence of hypoglycaemia, weight gain and other side effects related to individual agents. Type 2 diabetic subjects have great propensity to develop cardiovascular complications. Sulphonylureas, insulin and thiazolidinediones have all been associated with adverse cardiovascular outcomes in differing magnitude. It has been made mandatory by regulatory agencies to ensure cardiovascular safety of any new anti‐diabetic agent. Glucagon Like Peptide‐1(GLP‐1)‐based therapies have been able to address several of these issues. Incretin mimetics and Di Peptidyl Dipeptidase IV (DPP‐IV) inhibitors cause glucose‐dependent insulin secretion and glucagon suppression from beta and alpha cells of the pancreas respectively. They owe this property to their binding with G‐Protein‐coupled receptors leading to an increased amount of c‐AMP. They do not cause beta cell exhaustion. On the contrary such agents prevent beta cell apoptosis. Clinical trials have established the superiority of incretin mimetics particularly liraglutide against comparators including glimepiride, rosiglitazone and insulin Glargine in terms of efficacy. Furthermore, they have shown evidence towards beta cell protection, significant weight loss, minimal hypoglycaemia and favourable impact on surrogate markers of cardiovascular outcomes. DPP‐IV inhibitors have limited ability to achieve glycaemic targets. However, they are weight neutral, cause minimal hypoglycaemia and have some beneficial effect on beta cell function. Finally, they are very well tolerated.